Sensitivity of International Roughness Index to Distresses of Cement Concrete Road Surfaces - Peter Mucka (Communications - Scientific letters of the University of Zilina, 2016)
The paper examined the sensitivity of International Roughness Index (IRI) to the local discontinuities (various distresses, joints, joint and surface defects, other road features, etc.) of the cement concrete (CC) pavements. About 5 300 road records of total length 470 km from Long Term Pavement Performance (LTPP) program were processed. The raw profiles were separated into a random part and a distress part using the median filtering method. The median filter order was set to identify distresses of variable maximum width from 20 to 40 cm, and minimal height, 3 mm. About 26 000 distresses were separated and their dimensions were identified. The raw longitudinal road profiles were compared with the separated pure random parts. The mean relative increase in IRI caused by distresses was 3.3 % for maximum distress width 20 cm, 6.6 % (30 cm), and 10.7 % (40 cm).